BONE MARROW ASPIRATE CONCENTRATE FOR THE TREATMENT OF OSTEOCHONDRAL LESIONS OF THE TALUS: A SYSTEMATIC REVIEW OF OUTCOMES - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Monro, who removed a loose body from the ankle produced by traumatic injury, most likely provided the first description of an ankle OCL. Monro was the first person to describe an ankle OCL. The most important thing that was discovered as a result of this investigation was that there was a dearth of information in the published literature concerning the use of BMAC for the treatment of OLTs with very different indications, associated procedures, and outcome evaluations. This was the finding that stood out the most. This was the most important finding that came out of the research. On the other hand, the clinical trials that were examined indicated a variety of positive outcomes for the treatment of modestly sized chondral lesions, and there were no major difficulties noted in any of the studies. Only one of the studies that were included in this analysis was prospective and made use of a control group. This is despite the fact that all three of the studies that were included in this review had a quality that varied from moderate to high, as judged by the mCMS. According to the findings of this investigation, there is an alarming lack of long-term data and high-level evidence to support the deployment of this treatment approach. These two types of evidence are needed to lend support for the utilization of this therapeutic strategy. In spite of this, the evidence that was readily available revealed that BMAC was helpful for the treatment of ankle cartilage anomalies, albeit with varying degrees of success. This was the case despite the fact that there was no cure for the condition.